High School teachers' Experiences in classroom Ecology of Language Teaching: A Study from the Phenomenological Perspective - Mani Ram Sharma (Journal of English Education and Teaching, 2020)
The present study aims to look into ecological classroom practices adopted by teachers while teaching English language courses at colleges in Kathmandu, Nepal. The study specifically explains how three high school English teachers in the class felt about ecology of language teaching, how they experienced teaching, and how they provided meaning to it. Three high school English teachers’ experiences were recalled through an in-depth phenomenological interview. The results revealed that the need of classroom ecology was not emphasized. The teachers' experiences in the form of narratives, collected, transcribed, coded, thematic analyses and presented in the notion of  emerging themes that English language teaching helped to explore the effective classroom ecological practices in detail. The study is expected to contribute in making EFL teaching successful in linguistic landscapes of Nepal.